Haemolytic anemia secondary to thymoma without myasthenia gravis as parathymic syndrome: A case report (2016)
The case is presented of a 41 year-old male patient with chest pain, asthenia and adynamia. The imaging studies showed a mass in the anterior mediastinum, which according to the pathology report, was a thymoma. Also, the patient also had haemolytic anaemia and autoimmune hypothyroidism, and with no associated myasthenia gravis. © 2016 Published by Elsevier Españ a.